Creating and sharing legal knowledge in the Twelfth Century: Sankt Gallen, Stiftsbibliothek, 673 and its context - Dusil, Stephan; Thier, Andreas (Medieval law and its practice, 2023)
The Decretum Gratiani is the cornerstone of medieval canon law, and the manuscript St Gallen, Stiftsbibliothek, 673 an essential witness to its evolution. The studies in this volume focus on that manuscript, providing critical insights into its genesis, linguistic features, and use of Roman Law, while evaluating its attraction to medieval readers and modern scholars. Together, these studies offer a fascinating view on the evolution of the Decretum Gratiani , as well as granting new insights on the complex dynamics and processes by which legal knowledge was first created and then transferred in medieval jurisprudence. Contributors are Enrique de León, Stephan Dusil, Melodie H. Eichbauer, Atria A. Larson, Titus Lenherr, Philipp Lenz, Kenneth Pennington, Andreas Thier, José Miguel Viejo-Ximénez, John C. Wei, and Anders Winroth